Dynamic support design to mitigate rock burst - Valencia Chávez, Elvis William (2021)
In more than 100 years of underground mining, the mine has deepened, making larger openings by mechanization, changing the natural conditions of the rock mass, creating energy release problems known as rock bursting. The research methodology is quantitative, descriptive and explicatory. By applying observation techniques, the deformation of rocks was seen, classification and laboratory tests of rock mechanics, behavior of seismic waves and others were made, determining the dynamic properties of the rocks. The results indicate that the probability of rock bursting is weak to moderate, the strength of the intact rock is in the range of 92.5 to 163.7 MPa, the squeezing will be light to moderate and others. The support in most mines is static. Static support reaches a deformation of up to 16% for every 200.0 mm of length with a maximum energy absorption of 3 KN / m2, while dynamic support has a deformation greater than 600 mm with an energy absorption of up to 40 KN / m2. for this reason, it is shown that this is the best alternative to support for mining.